Рід Juncus L. (Juncaceae) у флорі України - Ольшанський, І.Г.; Федорончук, М.М. (Український ботанічний журнал, 2011)
Представлен конспект рода Juncus L. во флоре Украины. Для всех видов приведены номенклатурная цитация, основные синонимы, типы и сведения о распространении. Предложен ключ для определения видов. The paper provides the list of Juncus species known in Ukraine. For each species its nomenclatural citation, synonyms, types and distribution are given. The Key to species of Juncus is presented.